Atwood’s men meet the screen: revisiting literary and cinematic masculinities in The Handmaid’s Tale - Montenegro Bonilla, Joe (2020)
Margaret Atwood’s famous work, The Handmaid’s Tale, offers innovative and intriguing perspectives on gender and gender roles, as they are dramatized and problematized in the context of a dystopian society that in many ways is a projection of our own. Particu-larly interesting in the novel are the roles of men, represented by the principal male characters: the Commander, Nick, and Luke. As Atwood employs these personae to de-scribe at least three different manifestations of masculinity —all with their own con-flicts and possibilities—, the first season of the television version of the novel, created by Bruce Miller and released in 2017, explores, expands, and exploits various visions of manhood that help understand not only the protagonist’s but also the reader’s/viewer’s world. This paper is an attempt to establish a dialogue between Atwood’s and Miller’s viewpoints on masculinity through their portrayals of these three characters and their interactions with their protagonist and their context.